Design and Synthesis of BAW Bandpass Filter Based on Inline NRN and Dangling Resonator Topology - C. X. Yoon; S. Soeung; S. Cheab; P. W. Wong; C. C. D. Ling (Radioengineering, 2024)
In this paper, a novel inline network realization of non-resonating node (NRN) and dangling resonator (R) pair direct synthesis approach is presented. Arbitrary prescribed transmission zeros at real frequencies are realized through independently controlling the dangling resonators of the NRN-R pairs with impedance inverters between adjacent nodes. The bandpass element values for fourth order acoustic wave filter with a center frequency at 98 MHz are obtained through execution and mapping of the synthesis results based on the Generalized Chebyshev polynomials. The layout of prototype is presented. Finally, the prototype is constructed and measured using network analyzer to validate the proposed concept in realizing the BAW filter using Butterworth Lowpass Van Dyke (BVD) model. The filter has an insertion loss of 3.45 dB, a return loss of 8.5 dB, and two transmission zeros (TZs). In terms of implementation, this synthesis technique allows flexibility to synthesize and realize a conventional filter with transmission zeros as an inline network without cross couplings. This offers advantages in terms of size and cost reduction in filter production due to the inline resonator arrangement and reduced sensitivity in the design and tuning process.